Interferon‐β therapy specifically reduces pathogenic memory B cells in multiple sclerosis patients by inducing a FAS‐mediated apoptosis. Issue 9 (5th July 2016) - Rizzo, Fabiana; Giacomini, Elena; Mechelli, Rosella; Buscarinu, Maria Chiara; Salvetti, Marco; Severa, Martina; Coccia, Eliana Marina
Abstract : Growing evidences put B lymphocytes on a central stage in multiple sclerosis (MS) immunopathology. While investigating the effects of interferon‐β (IFN‐β) therapy, one of the most used first‐line disease‐modifying drugs for the treatment of relapsing‐remitting MS, in circulating B‐cell sub‐populations, we found a specific and marked decrease of CD27 + memory B cells. Interestingly, memory B cells are considered a population with a great disease‐driving relevance in MS and resulted to be also target of B‐cell depleting therapies. In addition, Epstein–Barr virus (EBV), associated with MS etiopathogenesis, harbors in this cell type and an IFN‐β‐induced reduction of the memory B‐cell compartment, in turn, resulted in a decreased expression of the EBV gene latent membrane protein 2A in treated patients. We found that in vivo IFN‐β therapy specifically and highly induced apoptosis in memory B cells, in accordance with a strong increase of the apoptotic markers Annexin‐V and active caspase‐3, via a mechanism requiring the FAS‐receptor/TACI (transmembrane activator and CAML interactor) signaling. Thus, efficacy of IFN‐β therapy in MS may rely not only on its recognized anti‐inflammatory activities but also on the specific depletion of memory B cells, considered to be a pathogenic cell subset, reducing their inflammatory impact in target organs.